Competencies of Higher Education Librarians to Research Support Services: A Narrative Review - Istiana, Purwani (Indonesian Journal of Librarianship, 2024)
Problem Statement: One essential need of university library users is library support for their research activities. This role of library requires librarians who are in charge of this service to have certain specialized competencies. Purpose: This study aims to present an overview of research support services and identify the competencies required for librarians to effectively deliver these services. Method: This study employed a narrative review as its research method. The data was collected from the Scopus database using the keywords research support services, research services, and academic library. The search results found 21 documents. Result: The analysis of the 21 documents shows that research support services are essential and part of the library's responsibilities. Librarians are required to have additional competencies to offer these services, including knowledge, understanding, and skill in all research stages, information retrieval and strategies, various literature review types, bibliometric and data analysis tools, the publishing process, data visualization tools, reference management software, intellectual property rights, publication impact, presentations, and other research tools. Conclusion: Research support services are one of the domains of higher education libraries. Research support services must be further developed as they are essential for assisting users with their research. Providing these services requires librarians to have certain competencies. The results of this study are useful for libraries in preparing librarian competencies for the implementation of research support services.